Behavioral and Psychological Symptoms of Dementia as a Means of Communication: Considerations for Reducing Stigma and Promoting Person-Centered Care - Warren, Alison (Frontiers in Psychology, 2022)
Dementia has rapidly become a major global health crisis. As the aging population continues to increase, the burden increases commensurately on both individual and societal levels. The behavioral and psychological symptoms of dementia (BPSD) are a prominent clinical feature of Alzheimer’s disease and related dementias (ADRD). BPSD represent a myriad of manifestations that can create significant challenges for persons living with dementia and their care providers. As such, BPSD can result in detriments to social interaction with others, resulting in harm to the psychosocial health of the person with dementia. While brain deterioration can contribute to BPSD as the disease progresses, it may be confounded by language and communication difficulties associated with ADRD. Indeed, when a person with dementia cannot effectively communicate their needs, including basic needs such as hunger or toileting, nor symptoms of pain or discomfort, it may manifest as BPSD. In this way, a person with dementia may be attempting to communicate with what little resources are available to them in the form of emotional expression. Failing to recognize unmet needs compromises care and can reduce quality of life. Moreover, failing to fulfill said needs can also deteriorate communication and social bonds with loved ones and caregivers. The aim of this review is to bring the differential of unmet needs to the forefront of BPSD interpretation for both formal and informal caregivers. The overarching goal is to provide evidence to reframe the approach with which caregivers view the manifestations of BPSD to ensure quality of care for persons with dementia. Understanding that BPSD may, in fact, be attempts to communicate unmet needs in persons with dementia may facilitate clinical care decisions, promote quality of life, reduce stigma, and foster positive communications.